Prove that 1square + 2square + 3square .......+nsquare =n(n+1)2n+1 divided by 6
Answers
Step-by-step explanation:
To prove ---->
--------------
n(n+1)(2n+1)
1²+2²+..................+n²=-----------------------
6
proof---> we prove it by pmi
---------
first we prove it for n=1
first term=1²=1
now putting n=1 in RHS
1(1+1)(2×1+1)
=---------------------
6
1(2)(2+1)
=--------------------
6
6
=--------=1
6
so given statement is true for n=1
now let given statement is true for n=k
k(k+1)(2k+1)
1²+2²+3²+........+k²=-----------------------
6
now we prove it is true for n=k+1
for this adding (k+1)² to both sides
k(k+1)(2k+1)
1²+2²+....+k²+(k+1)²=-------------------- +(k+1)²
6
k(2k+1)
=(k+1){--------------------------- +(k+1) }
6
k(2k+1) + 6 (k+1)
=(k+1) {_____________________}
6
2k²+ k + 6k + 6
= (k+1) (--------------------------------)
6
2k²+7k+6
= (k+1) (------------------------)
6
2k² +(4+3)k +6
=(k+1) {------------------------------}
6
2k²+4k+3k+6
=(k+1) {------------------------------}
6
2k(k+2) +3(k+2)
=(k+1) { _________________}
6
(k+2) (2k+3)
=(k+1) {________________}
6
{(k+1)+1}{(2k+2)+1}
=(k+1) [_____________________]
6
(k+1) {(k+1) +1 } {2(k+1)+1}
=--------------------------------------------------
6
so given statement is true for n=k+1 if it's true for n=k
so by principle of mathematical induction given statement is true for any natural number
Hope it helps you
Thanks for giving me chance to answer your question
another method is in attachment
![](https://hi-static.z-dn.net/files/dc3/dc7cd2042f2d83a692d8156d3d2ec805.jpg)
![](https://hi-static.z-dn.net/files/d76/a9971366f6ae76bfddccc8d81688dd80.jpg)
Answer:
Step-by-step explanation:
We have that:
1² + 2² + 3² + ... + n² = n(n + 1)(2n + 1)/6
We can prove this by induction. First, we need to show that it is true for n = 1.
1(1 + 1)(2 + 1)/6 = 1
So it is true for n = 1.
Now, we need to show that if it is true for a value, then it is true for the next value (which makes it true for all integers greater than that value as well).
Adding (n + 1)² to both sides gives us:
1² + 2² + 3² + ... + n² + (n + 1)² = n(n + 1)(2n + 1)/6 + (n + 1)²
Focusing on the RHS:
n(n + 1)(2n + 1)/6 + (n + 1)²
= n(n + 1)(2n + 1)/6 + 6(n + 1)²/6
= [n(n + 1)(2n + 1) + 6(n + 1)²]/6
= (n + 1)[n(2n + 1) + 6(n + 1)]/6. . . . . . . . . .Factor out (n + 1)
= (n + 1)(2n² + n + 6n + 6)/6
= (n + 1)(2n² + 4n + 3n + 6)/6
= (n + 1)[2n(n + 2) + 3(n + 2)]/6
= (n + 1)(2n + 3)(n + 2)/6
= (n + 1)[2(n + 1) + 1][(n + 1) + 1]/6
Since this result is the same as before except n + 1 is in n's spot. It is true for all n equal to or greater than 1! Q.E.D.
I hope this helps!